Generation of Artificial Thymic Organoids from Human and Murine Hematopoietic Stem and Progenitor Cells. Issue 4 (5th April 2022) - Montel‐Hagen, Amélie; Tsai, Steven; Seet, Christopher S.; Crooks, Gay M.
Abstract: The generation of T cells is a complex, carefully orchestrated process that occurs in the thymus. The ability to mimic T cell differentiation in vitro has opened up avenues to better understand different stages of thymopoiesis but has also enabled the in vitro production of mature T cells suitable for immunotherapy. Among existing protocols, the artificial thymic organoid (ATO) system has been shown to be the most efficient at producing mature conventional T cells. In this serum‐free model, human or murine hematopoietic stem and progenitor cells (HSPCs) are combined with a murine stromal cell line expressing a Notch ligand in a 3D cell aggregate. In ATOs, although only simple medium changes are required throughout the cultures, HSPCs differentiate into T cells with kinetics and phenotypes similar to those of endogenous thymopoiesis. This article describes protocols for the generation of ATOs from human and murine HSPCs. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Expansion and preparation of MS5‐hDLL4 or MS5‐mDLL4 cells Basic Protocol 2 : Isolation of human hematopoietic stem and progenitor cells (HSPCs; CD34+ cells) Support Protocol 1 : Transduction of human HSPCs (CD34+ cells) Basic Protocol 3 : Production of thymic progenitors and mature T cells from human HSPCs in artificial thymic organoids (ATOs) Support Protocol 2 : Phenotype analysis of human ATO cells by flow cytometry Basic Protocol 4 : Isolation of murine HSPCs (Lin‐ Sca1+ cKit+; LSK) and hematopoietic stem cells (LSK CD150+ CD48‐) Basic Protocol 5 : Production of thymic progenitors and mature T cells from murine HSPCs in ATOs Support Protocol 3 : Phenotype analysis of murine ATO cells by flow cytometry Alternate Protocol : Generation of ATOs from single HSPCs